LncRNA-CBR3-AS1 promotes and enhances the malignancy of ulcerative colitis via targeting miRNA-145-5p/FN1: LncRNA-CBR3-AS1 targets miR-145-5p/FN1 to affect colitis - Cao, Jingmei; Zhao, Qing; Jia, Qing; Li, Yiming (Cellular and Molecular Biology, 2023)
Growing evidence suggested that long non-coding RNA (lncRNA) played a crucial role in the progression of ulcerative colitis (UC). Therefore, the purpose of this study is to understand how the lncRNA CBR3-AS1, which has been found to be up-regulated in UC, contributes to the bio-progression of the disease. To determine the concentration and relationship of the lncRNA CBR3-AS1, miRNA-145-5p, and FN1 in the LPS-induced Caco-2 model cells, qRT-PCR was employed in this study. Starbase was used to predict the target sites of the lncRNA CBR3-AS1 and the miRNA-145-5p, and Targetscan was used to predict the probable linking points of the FN1 and the miRNA-145-5p, which was confirmed by a twofold luciferase reporter test. The vitality of Caco-2 cells was determined using the CCK-8 and FCM tests. Using the ELISA kit, TNF, IFN, IL-6, and IL-17 were identified. The results of the experiment show that in Caco-2 cells treated with 10 ng/mL LPS, LncRNA CBR3-AS1 was up-regulated. Additionally, Caco-2 cells' LPS-induced apoptosis and inflammatory response were inhibited by lncRNA CBR3-AS1 inhibition. Dual-luciferase reporter experiments demonstrated that miRNA-145-5p and lncRNA CBR3-AS1 might connect. Moreover, miRNA-145-5p, which was shown to be poorly expressed in UC, was found to suppress inflammatory and apoptotic responses in Caco-2 cells activated by LPS. It's significant that FN1 was confirmed to be miRNA-145-5p's downstream target. Sh-CBR3-AS1's inhibitory effects were reversed by miRNA-145-5p knockdown, and the effects of the miRNA-145-5p inhibitor were reversed by sh-FN1. In conclusion, LncRNA CBR3-AS1 may offer a unique method for treating UC by suppressing the function of miRNA-145-5p, which is implicated in the development of UC.